2020
DOI: 10.21873/anticanres.14562
|View full text |Cite
|
Sign up to set email alerts
|

Association of Caspase-8 Genotypes With the Risk for Nasopharyngeal Carcinoma in Taiwan

Abstract: Background/Aim: Accumulating evidence shows that caspase-8 (Cas-8) rs3834129 genotypes determine susceptibility to various cancers, but their association with nasopharyngeal carcinoma (NPC) has not been examined. We aimed at investigating the association of Cas-8 rs3834129 with NPC risk. Materials and Methods: Cas-8 rs3834129 genotypes and their associations with NPC risk were investigated among 176 NPC patients and 352 non-cancer subjects by the PCR-RFLP method. Additionally, the interaction of Cas-8 rs383412… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Moreover, Wang et al [8] also reached the same conclusion for esophageal cancer. While different conclusions were obtained, Lin et al [11] reported that there was no correlation between CAV1 (rs7804372) polymorphism and gastric cancer susceptibility. Hsu et al [12] evaluated the relationships between six single nucleotide polymorphism of the CAV1 gene and hepatocellular cancer risk in a Taiwanese population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, Wang et al [8] also reached the same conclusion for esophageal cancer. While different conclusions were obtained, Lin et al [11] reported that there was no correlation between CAV1 (rs7804372) polymorphism and gastric cancer susceptibility. Hsu et al [12] evaluated the relationships between six single nucleotide polymorphism of the CAV1 gene and hepatocellular cancer risk in a Taiwanese population.…”
Section: Discussionmentioning
confidence: 98%
“…[6] The carcinogenic role of CAV1 has been identified in several tumors, suggesting CAV1 as a novel therapeutic target for tumors. Several studies have explored the relationship between CAV1 polymorphisms and susceptibility to breast cancer, [7] esophageal carcinoma, [8] colorectal cancer, [9] gastric cancer, [10,11] hepatocellular, [12] and other cancers. [13,14] However, the results of the CAV1 rs7804372 (T29107A) polymorphism and susceptibility to digestive cancer remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, CDKs and cyclins are precisely regulated to guarantee accurate cellcycle progression. For instance, a subtle dysregulation in the G 1 to S phase transition due to cell cycle-related genes or proteins may be associated with various types of cancer (18)(19)(20)(21)(22)(23). In particular, cyclin D1 (CCND1) genotypes were found to be significantly associated with non-solid tumor childhood ALL risk (5).…”
Section: Discussionmentioning
confidence: 99%
“…Oral cancer XPC genotyping methodology. DNA from all participants was processed in typical polymerase chain reaction (PCR) processes as in our previous papers (25)(26)(27). The sequences of designed forward and reverse primers, corresponding restriction enzymes (New England BioLabs, Ipswich, MA, USA) and sizes of PCR products after enzyme digestion for oral cancer XPC genotyping identification are shown in Table II.…”
Section: Methodsmentioning
confidence: 99%